Pit patterns in rectal mucosa assessed by magnifying colonoscope are predictive of relapse in patients with quiescent ulcerative colitis. Issue 12 (8th May 2006) - Nishio, Y; Ando, T; Maeda, O; Ishiguro, K; Watanabe, O; Ohmiya, N; Niwa, Y; Kusugami, K; Goto, H
Abstract : Background: Relapse of ulcerative colitis is difficult to predict by routine colonoscopy. A high-resolution video-magnifying colonoscope with chromoscopy enables the observation of colorectal mucosal pit patterns. Aims: To investigate the association of pit patterns as assessed by magnifying colonoscopy (MCS) with histological inflammation and mucosal chemokine activity in patients with quiescent ulcerative colitis, and to prospectively analyse the prognostic factors that may predict exacerbations. Methods: MCS was performed in 113 patients with ulcerative colitis in remission. Pit patterns in the rectal mucosa were classified into four MCS grades on the basis of size, shape and arrangement. Mucosal interleukin (IL) 8 activity was measured in biopsy specimens of rectal mucosa and the specimens were assessed for histological disease activity. The patients were then followed until relapse or for a maximum of 12 months. Multivariate survival analysis was carried out to determine the independent predictors of clinical relapse. Results: A positive correlation was identified between MCS grade, histological grade (p = 0.001) and mucosal IL8 activity (p<0.001). Multivariate proportional hazard model analysis showed that MCS grade was a significant predictor of relapse (relative risk 2.06, p = 0.001). Kaplan–Meier estimate of relapse during 12 months of follow-up was found to increase with increasing MCS grade, with values of 0% for grade 1, 21% for grade 2, 43% for grade 3 and 60% for grade 4. Conclusion: MCS grading is associated with the degree of histological inflammation and mucosal IL8 activity in patients with quiescent ulcerative colitis, and may predict the probability of subsequent disease relapse in patients with ulcerative colitis in remission.